2019
DOI: 10.1029/2019ja026640
|View full text |Cite
|
Sign up to set email alerts
|

Preseismic Ionospheric Anomalies Detected Before the 2016 Taiwan Earthquake

Abstract: On 5 February 2016 (UTC), an earthquake with moment magnitude 6.4 occurred in southern Taiwan, known as the 2016 (Southern) Taiwan earthquake and 2016 Meinong earthquake. In this study, evidences of seismic earthquake precursors for this earthquake event are investigated. Results show that ionospheric anomalies in total electron content (TEC) can be observed before the earthquake. These anomalies were obtained by processing TEC data, where such TEC data are calculated from phase delays of signals observed at d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Some TEC anomalies were observed within one day after the earthquakes due to acoustic resonance of the aftershocks. Reference [10] investigated the TEC variation related to the February 5, 2016 (UTC) Tainan earthquake with ML = 6.6. The TEC data were calculated using the phase delays of the signals observed from the densely arranged ground-based stations in Taiwan for GNSS.…”
Section: B Related Studies Of Tec Precursorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some TEC anomalies were observed within one day after the earthquakes due to acoustic resonance of the aftershocks. Reference [10] investigated the TEC variation related to the February 5, 2016 (UTC) Tainan earthquake with ML = 6.6. The TEC data were calculated using the phase delays of the signals observed from the densely arranged ground-based stations in Taiwan for GNSS.…”
Section: B Related Studies Of Tec Precursorsmentioning
confidence: 99%
“…(6) Their results demonstrated that the TEC precursors were mostly located over the epicenter. Moreover, TEC data processing was complicated, which could require considerable examination time to sufficiently determine the earthquake TEC precursors instead of short-term prediction, e.g., within 1 h before an earthquake [10]. Therefore, the aim of this study is to identify the ionospheric TEC precursors, which are generally detectable, using a type of mathematical tool without the disadvantage of the previous methods so that the research method and the data acquisition should be not as expensive as possible and the data processing is not complicated thereby making it a better survey method dealing with TEC precursors.…”
Section: B Related Studies Of Tec Precursorsmentioning
confidence: 99%
“…Thus we know that TEC disturbances spread out to almost all directions from the epicenter, with the speed of several hundreds of meters to several kilometers per second. Pre-seismic ionospheric anomalies appearing several hours to several days before the main shock have also been reported by lots of researchers as observed in TEC or other ionospheric parameters (De Santis et al 2019;Liu et al 2004Liu et al , 2006aGoto et al 2019;Heki & Enomoto 2013). Pre-seismic TIDs are often reported in time of the probability of a new EQ precursor.…”
mentioning
confidence: 76%
“…CRA to detect total electron content (TEC) anomalies before large earthquakes is based on the very long baseline interferometry's concept and spreading spectrum communications technology. It has been implemented to report in the references: 2016, Iwata & Umeno (hereafter I & U16) [1], 2017, Iwata & Umeno (hereafter I & U17) [2], and 2019, Goto, et al, (hereafter Goto et al 2019) [3].…”
Section: Introductionmentioning
confidence: 99%